Plantation-Based Jhumias Rehabilitation in Tripura: Exploring the Challenges and Traditional Practices in Overcoming Crises - Kuki, Vanlalrema; Bhowmik, Indraneel (Indian Journal of Agroforestry, 2025)
Plantation crop cultivation is becoming a significant occupation in Tripura among the Scheduled Tribes owing to its potential economic viability. The state government adopted a plantation model to rehabilitate the jhumias through various agencies while working with the Tribal Welfare Department and the Tripura Tribal Areas Autonomous District Council. However, the cultivation has threats. The beneficiaries met different challenges during plantation development under various models. The present study revealed that the low quality of saplings was considered the foremost challenge during rehabilitation. Besides, strong wind, poor management, insect menace, lack of storage facilities, infrastructure and institutional challenges are other potential risks and difficulties leading to losses. The most common response strategies adopted by the beneficiaries are marketing-based response and production-related mechanisms. They are also using traditional knowledge to avoid economic and farms related problems.